2018
DOI: 10.1093/cid/ciy676
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Indoleamine 2,3-Dioxygenase Activity Is Associated With the Size of the Human Immunodeficiency Virus Reservoir in Patients Receiving Antiretroviral Therapy

Abstract: We observed a positive correlation between IDO activity and total HIV DNA in blood, highlighting the important role of immunometabolic aberrations in HIV persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 40 publications
7
37
1
Order By: Relevance
“…The plasma K/T ratio was significantly higher in South African MDR-TB patients both with and without HIV coinfection versus controls ( Figure 3A). Persons with TB disease coinfected with HIV had a higher plasma K/T ratio versus persons with TB disease alone (P = 0.01), consistent with prior observations that HIV also induces tryptophan catabolism (28,29). The plasma K/T ratio again demonstrated excellent classification accuracy for active TB disease (AUC = 0.92; Figure 3C), and a cutoff of 0.03 had a sensitivity of 99% in both cohorts.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The plasma K/T ratio was significantly higher in South African MDR-TB patients both with and without HIV coinfection versus controls ( Figure 3A). Persons with TB disease coinfected with HIV had a higher plasma K/T ratio versus persons with TB disease alone (P = 0.01), consistent with prior observations that HIV also induces tryptophan catabolism (28,29). The plasma K/T ratio again demonstrated excellent classification accuracy for active TB disease (AUC = 0.92; Figure 3C), and a cutoff of 0.03 had a sensitivity of 99% in both cohorts.…”
Section: Resultssupporting
confidence: 84%
“…If tryptophan catabolism modulates T cell responses to create tolerance, such immune modulation may be protective in the central nervous system, where robust inflammatory responses are generally detrimental (47). In conditions such as HIV and pregnancy, which similarly induce IDO-mediated tryptophan catabolism (29,44), further study is needed to determine whether this may contribute to the elevated TB progression risk observed in these populations (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that IDO-1 activity and Treg frequency were strongly correlated with plasma βDG. We, as well as others, have shown that increased IDO-1 activity is linked to an increased frequency of Tregs, epithelial gut damage, degree of microbial translocation, immune activation, HIV disease progression, and HIV reservoir size [15,25,28,[31][32][33]. Because IDO-1 is known to be expressed in myeloid cells, which also express βDG receptors, these findings suggest that elevated βDG may participate in the induction of IDO-1 activity.…”
Section: Discussionsupporting
confidence: 60%
“…Although it was not mechanistically interrogated, a positive association between plasma indoleamine 2,3-dioxygenase (IDO) activity (an immunoregulatory enzyme that metabolizes tryptophan) and total HIV DNA in peripheral blood has been established. 68 Impaired intestinal barrier integrity is a classical feature of HIV infection, characterized by dysbiosis and increased microbial by-products that drive systemic and mucosal in ammation. 69,70 Microbes with the capacity to catabolize tryptophan have been linked to adverse HIV disease progression, 71 at least in part due to induction of IDO1 that interferes with Th17/Treg balance in the periphery and gut.…”
Section: Discussionmentioning
confidence: 99%